Healthy Nests Transition to Parenthood Program: A Mixed-Methods Study. Issue 4 (2nd October 2017) - Linville, Deanna; Todahl, Jeff; Brown, Tiffany; Terrell, Lorin; Gau, Jeff
ABSTRACT: Intimate partner relationship distress is associated with a wide range of negative adult and child outcomes. The transition to parenthood is often a time in the life of a couple where relationship distress increases and satisfaction and intimacy decrease and thus is an ideal time for targeted intervention. The Healthy Nests (HN) intervention is a three-meeting, strength-focused couples intervention for first-time parents designed to decrease maladaptive relationship conflict and increase couple well-being. The authors conducted a mixed-methods exploratory study investigating participants' overall experiences with the HN intervention and measured outcomes associated with relationship satisfaction, help seeking, father involvement, substance use, and depression. A total of 130 parents (65 dyads) participated in a randomized intervention and educational materials–only alternative intervention. Twenty dyads were interviewed as a part of the qualitative portion of the study. While the authors did not find significant quantitative effects on key outcomes, the qualitative findings suggested that participants had a positive experience with the HN intervention and indicated it was useful to have designated time and space to communicate as a couple. Qualitative findings also suggest that the focus on "aspects of strength" and "areas of change" in their relationship was useful. Implications for practice, research, and training are discussed.